Effect of Concrete-Exemplar Model on Conceptual Understanding of Volumetric Analysis Concept among Federal College of Education Students in North-West, Nigeria (Federal University Gusau Faculty of Education Journal, 2025)
This study Effect of Concrete-Exemplar Model on Conceptual Understanding of Volumetric Analysis Concept among Federal College of Education Students in North-West, Nigeria. The study adopted pretest and posttest quasi experimental control group design. The population of the study comprised 718 (310 male and 408 female) NCE I Chemistry students from all the six Federal Colleges of Education in North- West, Nigeria. The sample of one hundred and ten (110) NCE Chemistry students were purposively selected from the target population. The experimental group was exposed to concrete exemplar model while the control group was exposed to conventional laboratory teaching method. Chemistry Conceptual Understanding Inventory (CCUI) with reliability coefficient of 0.80 respectively used to measure conceptual understanding of Students on the concept volumetric analysis. Cronbach’s Alpha reliability coefficient test. The Study was guided by two objectives, research questions, and corresponding null hypotheses, respectively. Two research questions were answered using descriptive statistics of mean and standard deviation and two null hypotheses were tested at p < 0.05 level of significance using t-test inferential statistics. The results among others revealed a significant difference between the conceptual understanding of experimental group and control group (p= 0.01 < 0.05). Based on these findings it was concluded that students taught Volumetric Analysis concept using concrete exemplar model had better conceptual understanding of the concept than those taught same concept using conventional laboratory method. The study, therefore recommended among others that, the use of concrete exemplar model should be encouraged among chemistry teachers at NCE level in teaching volumetric analysis concept to enhance students’ meaningful learning and conceptual understanding.